2019
DOI: 10.1002/bjs5.50154
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score analysis of non‐anatomicalversusanatomical resection of colorectal liver metastases

Abstract: Background There are concerns that non‐anatomical resection (NAR) worsens perioperative and oncological outcomes compared with those following anatomical resection (AR) for colorectal liver metastases (CRLM). Most previous studies have been biased by the effect of tumour size. The aim of this study was to compare oncological outcomes after NAR versus AR. Methods This was a retrospective study of consecutive patients who underwent CRLM resection with curative intent from 1999 to 2016. Data were retrieved from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Of interest is the global trend towards parenchymal-preserving surgery over time. 13,20 Most studies have demonstrated a decrease in morbidity and mortality with parenchymal-preserving or nonanatomical resections, without compromising on margin status. 13,20 However, we found across the two periods a trend of proportionally more segmentectomies than subsegmental resections, and overall more extended hepatectomies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of interest is the global trend towards parenchymal-preserving surgery over time. 13,20 Most studies have demonstrated a decrease in morbidity and mortality with parenchymal-preserving or nonanatomical resections, without compromising on margin status. 13,20 However, we found across the two periods a trend of proportionally more segmentectomies than subsegmental resections, and overall more extended hepatectomies.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 Most studies have demonstrated a decrease in morbidity and mortality with parenchymal-preserving or nonanatomical resections, without compromising on margin status. 13,20 However, we found across the two periods a trend of proportionally more segmentectomies than subsegmental resections, and overall more extended hepatectomies. This may reflect more complex disease in the latter period, with fewer tumours amenable to subsegmental resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective case–control study design was adopted by including all patients from January 1999 to December 2012 at Royal North Shore Hospital with either synchronous or metachronous liver‐only metastatic CRC from two previously described prospectively maintained databases of resected primary CRC 11 and CRLM. 12 Patients were excluded if their primary pathology tumour was anal in origin. An equal number of ‘control’ patients matched on age, sex, grade, T and N stage of their primary CRC (AJCC staging guidelines, 7th ed.…”
Section: Methodsmentioning
confidence: 99%